2012
DOI: 10.1111/j.1439-0507.2011.02165.x
|View full text |Cite
|
Sign up to set email alerts
|

Species and susceptibility distribution of 1062 clinical yeast isolates to azoles, echinocandins, flucytosine and amphotericin B from a multi‐centre study

Abstract: Descriptive values were determined for eight antifungal agents within the course of a multi-centre study encompassing 1062 German and Austrian clinical yeast isolates. Candida albicans (54%) was the predominant species isolated followed by Candida glabrata (22%), Candida parapsilosis (6%), Candida tropicalis (5.7%), Candida krusei (4.3%), as well as eleven further candidal and four non-Candida yeast species. While 519 (48.9%) isolates were tested susceptible to all antifungals tested, no isolate was found to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
38
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 61 publications
12
38
0
1
Order By: Relevance
“…As observed in Table 3, among the NCAC species (n=32), 31.2% of the isolates demonstrated SDD to fl uconazole, with 3.1% being resistant to amphotericin B (which corroborates published reports of high resistance of these species to antifungal agents) 9,13 . None of the isolates of C. glabrata were susceptible to fl uconazole, although 80% were SDD and 20% were resistant, in agreement with the fi ndings of other authors who described the low sensitivity of this species to triazol 32,33 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As observed in Table 3, among the NCAC species (n=32), 31.2% of the isolates demonstrated SDD to fl uconazole, with 3.1% being resistant to amphotericin B (which corroborates published reports of high resistance of these species to antifungal agents) 9,13 . None of the isolates of C. glabrata were susceptible to fl uconazole, although 80% were SDD and 20% were resistant, in agreement with the fi ndings of other authors who described the low sensitivity of this species to triazol 32,33 .…”
Section: Discussionsupporting
confidence: 84%
“…There have been, however, increases in HI caused by non-C. albicans Candida (NCAC) species such as C. tropicalis, C. glabrata, C. parapsilosis, and C. krusei [6][7][8] . The occurrence of infections caused by these yeasts is relevant to HI vigilance because these micro-organisms have varying virulence attributes and profi les of antifungal drug sensitivity, including recent reports of resistance to the principal antifungal drugs currently administered in hospitals 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…The broad use of triazoles, especially fluconazole, has given rise to concerns regarding the emergence of resistance. 35 We found the overall resistance to amphotericin B to be 8.9%, which is similar to the findings of the German-Austrian multicentre study 31 which showed nearly 11.2% Candida isolates to be amphotericin B-resistant. In such a scenario of high frequency of resistance, need of the hour is to ensure that identification, isolation of Candida species and evalution of treatment options should become an integral part of clinical microbiology services.…”
Section: Discussionsupporting
confidence: 87%
“…In a large study 30 comprising of 1106 cases of candidemia over a nine year period, all the C.albicans strains were found to be susceptible to amphotericin B, fluconazole and voriconazole, while among the NAC, 88.6% were sensit ive to voriconazole, and 68.8% to fluconazole. Similar higher frequencies of resistance among NAC compared to C.albicans, has been observed in recent years from Europe 31 and China. 32 Resistance to azole group of antifungal agents can be due to quantitative or qualitative modifications of target enzymes, low access of the drug to the target, or a combination of these mechanisms.…”
Section: Discussionsupporting
confidence: 82%
“…2 To date, only limited data are available on the sensitivity of C. krusei to posaconazole. 3 As pharmacokinetic measurements were not evaluated in her daily routine, we further hypothesized that blood levels could have been too low to prevent infection. Nevertheless, in vitro testing of antifungal drug sensitivity in our case revealed sensitivity to posaconazole, supporting the idea of insufficient drug availability.…”
mentioning
confidence: 99%